Co-Designing Checklists to Understand Organizational Challenges and Opportunities around Fairness in AI - Madaio, Michael; Stark, Luke; Vaughan, Jennifer Wortman; Wallach, Hanna (CHI Conference on Human Factors in Computing Systems, 2020)
Many organizations have published principles intended to guide the ethical development and deployment of AI systems; however, their abstract nature makes them difficult to operationalize. Some organizations have therefore produced AI ethics checklists, as well as checklists for more specific concepts, such as fairness, as applied to AI systems. But unless checklists are grounded in practitioners’ needs, they may be misused. To understand the role of checklists in AI ethics, we conducted an iterative co-design process with 48 practitioners, focusing on fairness. We co-designed an AI fairness checklist and identified desiderata and concerns for AI fairness checklists in general. We found that AI fairness checklists could provide organizational infrastructure for formalizing ad-hoc processes and empowering individual advocates. We discuss aspects of organizational culture that may impact the efficacy of such checklists, and highlight future research directions.
CHI 2020 Best Paper Award